Confirmatory Factorial Analysis of the Personal Spirituality Scale in Puerto Ricans Adults - González-Rivera, Juan (2018)
Spirituality is defined as the multidimensional capacity of search for meaning and connection in relationships with oneself, other people, nature or the sacred. The aim of this study was to analyze the reliability and factor structure of Personal Spirituality Scale (PSS-R) in a sample of Puerto Ricans adults. A total of 577 Puerto Ricans participated in this psychometric study. The results confirmed that the PSS has a multidimensional structure. These dimensions were Intrapersonal Spirituality, Interpersonal Spirituality and Transpersonal Spirituality. The twelve items complied with the criteria of discrimination. The reliability index obtained fluctuated between .81 to .95. The PSS-R has appropriate psychometric properties useful for validation studies. It can be used in different lines of research, theoretical as well as applied.